STANDARDS OF PREPARATION FOR THE FORMATION OF SOCIAL ACTIVITY AMONG FUTURE PRIMARY SCHOOL TEACHERS - Otabek Shanazarov (Proximus Journal Publishing, 2024)
This article substantiates the scientific, theoretical, pedagogical and psychological standards for the formation of social activity skills in primary school students through pedagogical research
Keywords: Primary school students; students; regulatory documents in the field of education